PENGARUH MEDIA YOUTUBE PADA VIDEO TUTORIAL VAPING OFFICIAL VGOD TERHADAP TINGKAT PENGETAHUAN VAPERS TANGERANG SELATAN (SURVEI DILAKUKAN PADA AVTA ASOSIASI VAPORIZER TANGERANG) - Liliyana Liliyana; Muhammad Nur Imam (Jurnal Akrab Juara, 2018)
This study aims to find out how the influence of real media on youtube video vaping tutorials belonging to the official channel vgod to the level of knowledge of the vectors of South Tangerang. But with the sophistication of digital media, one of them through video, we can communicate, exchange information and even learn with anyone who is in other countries, and youtube serves as a research object because according to a survey that has been done on alexa. Com youtube ranking as the second site most visited by netizens around the world, so from youtube it is made object of research which then become subject of research is on vape user or vapers incorporated in AVTA community. Keywords: Tutorial, Vaporizer, Youtube